Equilibrium coalitional behavior - Mert Kimya (Theoretical Economics, 2020)
I develop two related solution concepts, equilibrium coalitional behavior and credible equilibrium coalitional behavior, which capture foresight and impose the requirement that each coalition in a sequence of coalitional moves chooses optimally among all its available options. The model does not require, but may use, the apparatus of a dynamic process or a protocol that specifies the negotiation procedure underlying coalition formation. Therefore, it forms a bridge between the non-cooperative and the cooperative approaches to foresight.
Keywords: C70; C71; C72; D71; 330; Coalition formation; farsightedness